Temporal and spatial variations of GPS TEC and phase during auroral substorms and breakups - Prikryl, P.; Weygand, J.M.; Ghoddousi-Fard, R.; Jayachandran, P.T.; Themens, D.R.; McCaffrey, A.M.; Kunduri, B.S.R.; Nikitina, L. (Polar Science, 2021)
Temporal and spatial changes of GPS total electron content (TEC) and phase variation, called phase scintillation, during auroral substorms and breakups are investigated in the context of horizontal equivalent ionospheric currents and estimated vertical current amplitudes derived from ground magnetometer network using the spherical elementary current method. GPS phase scintillation is computed for sampling rate of 50 Hz by specialized GPS scintillation receivers from the Canadian High Arctic Ionospheric Network (CHAIN). A proxy phase scintillation index is obtained from dual frequency measurements of geodetic-quality GPS receivers sampling at 1 Hz, which include globally distributed receivers of RT-IGS network that are monitored by the Canadian Geodetic Survey in near-real-time. Based on analysis of four cases, it is shown that GPS phase scintillation maps to regions of strong westward electrojet and to the poleward edge of the eastward electrojet. For substorm onsets, auroral breakups and substorm intensifications, the ionospheric pierce points with moderate to strong phase scintillation associated with TEC enhancements map to regions of intense westward electrojet interfacing with the eastward electrojet near the boundaries between downward Region 1 and upward Region 1/Region 2 currents in the Harang discontinuity region, where intense auroral emission was observed for some of the cases studied. Energetic particle precipitation in this dynamic region results in steep electron density gradients and drifting irregularities that are the cause of GPS phase variation. journal article